Crystallization Mechanism of CVD Si3N4–SiCN Composite Ceramics Annealed in N2 Atmosphere and Their Excellent EMW Absorption Properties. Issue 8 (21st April 2016) - Xue, Jimei; Yin, Xiaowei; Pan, Hongxing; Liu, Xiaofei; Zhang, Litong; Cheng, Laifei
Abstract : To tailor a new electromagnetic wave (EMW) absorbing material with lower reflection coefficient (RC) and larger operating frequency band, the CVD Si3 N4 –SiCN composite ceramics were prepared from SiCl4 –NH3 –C3 H6 –H2 –Ar system and then annealed at the temperatures of 1400–1700°C in N2 atmosphere. Effect of the annealing temperatures on the microstructure, phase composition, permittivity, and microwave‐absorbing properties of the ceramic were investigated. Results showed that the CVD Si3 N4 –SiCN ceramics gradually crystallized into nanosized SiC grains, Si3 N4 grains and graphite ( T ≤ 1600°C), and then the grains grew up at T = 1700°C. The permittivity, dielectric loss, and electrical conductivity of as‐annealed CVD Si3 N4 –SiCN ceramics ( T ≤ 1600°C) increased firstly due to the formation of conductivity and polarity network and the increase in nanograin boundary, and then decreased at 1700°C because of the growth of nanograins and the disappearance of nanograin boundary. The minimal RC and effective absorption bandwidth of the as‐annealed CVD Si3 N4 –SiCN ceramic at 1600°C was −41.67 dB at the thickness of 2.55 mm and 3.95 GHz at the thickness of 3.05 mm, respectively, demonstrating that the totally crystallized CVD Si3 N4 –SiCN ceramic ( T = 1600°C) had the superior microwave‐absorbing ability.